The Ripakawing Tradition of the Bugis Migrants in Tanete Riaja District, Barru Regency: A Legal Family Analysis in Islam - Nuramila, Nuramila; Budiman, Budiman; Wahidin, Wahidin (Jurnal Marital: Kajian Hukum Keluarga Islam, 2024)
This study aims to examine the ipalai tapi' tradition in marriage in Suppa District, Pinrang Regency, and analyze it from the perspective of Islamic law. This research employs field research methods with a qualitative descriptive approach. Primary data were obtained through observation, interviews with the community and cultural figures, and documentation. Secondary data were obtained from archives, journals, and previous studies. The findings indicate that the ipalai tapi' tradition emerged as a response to the high divorce rate and other household issues, functioning as a symbol and prayer to protect the newlyweds' household from undesirable matters. The ipalai tapi' process is carried out after the marriage contract, using a tapi' cloth that is draped over the bride and groom and then sewn by a community or family elder, symbolically binding the couple to ensure a lasting relationship. The Islamic legal analysis categorizes this tradition as al-urf shohih, which means permissible customs.This study recommends that the ipalai tapi' tradition be maintained and preserved as part of local culture that does not contradict Islamic teachings.